(untitled) (Research, Society and Development, 2021)
The adenomatoid odontogenic tumor is a benign epithelial pathology that comprises 3 to 7% of odontogenic tumors. It has the characteristic of slow and progressive growth and almost no symptoms, being more frequent in women especially in the first two decades of life. Also, the anterior region of the maxilla is the anatomical location mostly affected. A white female patient, 16 years old, presented absence of the canine, first, and second maxillary premolars on the right side, prolonged retention of the right upper deciduous second molar, volumetric increase in the buccal and palatal alveolar ridge with extension to the bottom of the right maxillary vestibule, being diagnosed after the incisional biopsy as an adenomatoid odontogenic tumor. Considering the clinical and radiographic examination, it was decided to perform decompression of the lesion before performing enucleation and curettage.